Actuation of a carbon/epoxy beam using shape memory alloy wires. (January 2019) - Damansabz, Reza; Taheri-Behrooz, Fathollah
Shape memory effect of NiTi wires is utilized to design various smart composite structures. In these systems, smart wires can induce strains in the host structure by their inherent shape memory effect and phase transformation at elevated temperatures. This article presents an experimental and numerical study on the actuation capability of shape memory alloy wires embedded in the carbon/epoxy composite. In the experimental part, hybrid shape memory alloy/carbon/epoxy composite specimens are fabricated and examined to measure induced strains in the host structure by the phase transformation of the shape memory alloy wires. Hybrid composite specimens were clamped at one end, and the shape memory alloy wires were activated using electrical resistive heating. Numerical simulations were carried out using ABAQUS software to simulate the actual thermomechanical behavior of the hybrid composite specimens. A three-dimensional finite element model based on cohesive zone modeling is used to predict interfacial debonding in hybrid composite plates. The results of the parametric study suggest that by increasing Young's modulus of the host composites, the amount of the induced strain decreases rapidly. However, for Young's moduli more than 20 GPa, the induced strain will stay almost constant. Moreover, it was confirmed that increasing the shape memory alloy pre-strain without controlling the actuation temperature may result in the reduction of induced strain in the host composites.